The impact of entrepreneurship educations on entrepreneurial capacity and self-employment - Olaiya, Mudashir Gafar (2015)
Real Estate Management (REM) practice is being increasingly challenged, as a result of the economic recession, encroachment of quacks and allied professionals as well as the technological revolution of the contemporary knowledge-based economy. This implies that conformist approach to the REM training might not be enough to guarantee REM students employment prospect. More so, the issue of graduates’ employability in the job market is becoming more competitive in Malaysia. However, entrepreneurship education (EE) introduced in the Malaysian Higher learning institutions with the intention of boosting the employability of the graduates. In spite of the above initiative, impact assessment of the EE is still ambiguous, particularly, in the REM discipline. Hence, an absence of a common assessment framework to evaluate diverse EEs registered in the literature. Therefore, the research aimed to assess perception of the REM students on the impact of entrepreneurship education on the entrepreneurial capacity and self-employment intention and to propose an Objective-based Entrepreneurship Education Assessment Model (OBEEAM). The research employed quantitative research approach and ex-post research design. Hence, purposive sample technique applied to collect data on the sample size of 437 REM students through a cross-sectional survey in the four Malaysian public universities. SPSS 22.0 and Structural Equation Modeling tools of analysis were used to analyse, data collected, proposed OBEEAM and test of the nine research hypotheses empirically. The findings indicated a positive impact of entrepreneurship education on the perception of REM students’ entrepreneurial capacity and self-employment intention as a career option. Despite, the skills of creativity and innovation in the idea development, risk taking proficiency and practical workshop practice were somewhat weak. Therefore, the need for more practical initiative exercises such as extended entrepreneurship teaching in the core courses and across the years of REM programmes recommended. This could provide the innovation required for the development of dynamic future real estate-entrepreneurs in Malaysia. The research’s novelty is the proposed multidirectional OBEEAM that had integrated the core values and drivers of entrepreneurship teaching and self-employment intention; it could be adopted, adapted and implemented for the assessment of EEs in any academic field of studies.